2013
DOI: 10.1080/09583157.2013.852652
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of a new mosquitocidal bacterium strain ofEnterobacter cloacaeVCRC-B519 from marine soil

Abstract: A novel mosquitocidal bacterium was isolated from marine soil. 16S rRNA gene sequence alignment depicted that this isolate belonged to the strain, Enterobacter cloacae VCRC-B519 (NCBI: KC119193). Biochemical studies such as bacterial growth, biomass production and protein (toxin) synthesis showed that the strain is plausibly useful for mosquito control. It showed an increasing pattern of toxicity for Culex quinquefasciatus, Anopheles stephensi and Aedes aegypti, without negative effects for non-targeted organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Totally 140 soil samples were collected including red, clay loam, clay, sandy and loamy soil. These were screened for mosquitocidal bacteria, using serial dilution method (Poopathi et al, 2014;Hemaladkshmi et al, 2023). Bacterial colonies were isolated and cultured till 72 hr in NYSM broth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally 140 soil samples were collected including red, clay loam, clay, sandy and loamy soil. These were screened for mosquitocidal bacteria, using serial dilution method (Poopathi et al, 2014;Hemaladkshmi et al, 2023). Bacterial colonies were isolated and cultured till 72 hr in NYSM broth.…”
Section: Resultsmentioning
confidence: 99%
“…One g of each soil sample was weighed and serially diluted (10 -3 ) (Poopathi et al, 2014). Using spread plate method 100 μl of the dilution was spread on nutrient yeast extract salt medium (NYSM) and incubated for 24 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A novel cyclodepsipeptide named iso‐isariin D ( 58 ) together four known destruxin cyclodepsipeptides ( 59 – 62 ) were isolated from Beauveria felina EN‐135, a pathogenic fungus from a marine bryozoan and prominent in insecticidal activity tests [113] . Enterobacter cloacae VCRC−B519 obtained from marine soil was regarded as effective mosquitocidal bacterium, three peptides [114] isolated are thought to be related to the insecticidal activity of this bacteria. Study among marine soil collected from Pondicherry found a unique mosquitocidal bacterium and identified to be Bacillus cereus VCRC‐B520, isolation guided by its insecticidal activity discovered an insecticidal protein, namely “Cry4Aa”, [115] which can cause mosquito susceptibility of Culex quinquefasciatus.…”
Section: Insecticidal Metabolites and Bio‐control Strains From Marine Microorganismsmentioning
confidence: 99%